P04.04 Multifunctional antibody construct for in vivo targeting of dendritic cells as a therapeutic vaccination strategy in AML. (1st October 2020) - Schmitt, S; Lohner, A; Deiser, K; Maiser, A; Rothe, M; Augsberger, C; Moosmann, A; Leonhardt, H; Fenn, N; Griffioen, M; Hopfner, K; Subklewe, M
Abstract : Background: Dendritic cells (DCs) are antigen-presenting cells that induce antigen-specific T-cell responses. Therefore, they are used as tools and targets for anti-tumor vaccination. In contrast to T-cell based immunotherapies, that are often limited to surface antigens, DC-based vaccination strategies open up new therapeutic options by utilizing highly abundant intracellular tumor antigens as a target source. Among those, recent interest has been focused on the identification of neoantigens derived from tumor-specific mutations. Especially mutated Nucleophosmin 1 (ΔNPM1) is a considered candidate for targeted therapy in acute myeloid leukemia (AML). We developed a multifunctional antibody construct consisting of a peptide domain including a variable T-cell epitope that is fused to an αCD40 single chain variable fragment (scFv) with agonistic function to target and activate dendritic cells in vivo. To potentiate therapeutic efficacy, toll-like receptor (TLR) agonists can be attached as co-stimulatory domains, thereby aiming to enhance cross-presentation of conjugated (neo)antigens to CD8+ T cells. Materials and Methods: Flow cytometry and microscopy-based binding and internalization experiments were performed using monocyte-derived dendritic cells (moDCs). Upregulation of surface markers (CD80, CD83, CD86, HLA-DR) as well as cytokine secretion (IL-6 and IL-12) indicated DC maturation. To validate peptide processing and presentation, moDCs were co-cultured with autologous as well as allogeneic T cells. IFN-γ and TNF-α secretion served as a readout for T-cell activation, peptide-MHC multimer staining for T-cell proliferation. Results: For proof-of-principle experiments, the multispecific antibody derivative was developed by fusing the αCD40 scFv to a cytomegalovirus (CMV)-specific peptide. The αCD40.CMV construct bound CD40 agonistically and showed efficient internalization into early endosomal compartments on immature moDCs. In co-cultures of immature and mature moDCs with autologous or allogeneic T cells, αCD40.CMV induced a significantly increased T-cell activation and proliferation compared to the control. The co-administration of αCD40.CMV with various TLR agonists as vaccine adjuvants resulted in a significant upregulation of DC maturation markers in comparison to αCD40.CMV only. Interestingly, not all adjuvants were able to enhance the T-cell response. To translate this principle to the AML setting, the CMV peptide sequence was replaced with the ΔNPM1-derived and HLA-A*02:01-binding neoantigen CLAVEEVSL. Cross-presentation to CD8+ T cells transduced with a ΔNPM1-specific T-cell receptor was proven by IFN-γ and TNF-α secretion in co-cultures with moDCs that have been pre-incubated with αCD40.ΔNPM1. The optimal vaccine adjuvant has yet to be identified. Conclusions: We successfully demonstrated the development of a multifunctional antibody construct that specifically targets and stimulates DCs by an agonistic αCD40 scFv. It simultaneously delivers a T cell-specific peptide with a vaccine adjuvant to induce an efficient T-cell response. As neoantigens are promising targets and under intense investigaton, the αCD40.ΔNPM1 fusion protein is of high therapeutic interest. Thus, our approach displays a promising DC vaccination option for the treatment of AML. Disclosure Information: S. Schmitt: None. A. Lohner: None. K. Deiser: None. A. Maiser: None. M. Rothe: None. C. Augsberger: None. A. Moosmann: None. H. Leonhardt: None. N. Fenn: None. M. Griffioen: None. K. Hopfner: None. M. Subklewe: None.